Winning At Innovation: The A-to-F Model - Bes, Fernando Trias de; Kotler, Philip (London: Palgrave Macmillan, 2012)
Innovation is a responsibility normally assigned to R&D departments but this is not enough. Companies need a systematic framework so innovation can occur at different levels of the organization. The world's leading expert in marketing and innovation Philip Kotler, and Fernando Trias de Bes together present a revolutionary model for innovation.
Innovation is a responsibility normally assigned to R&D departments but this is not enough. Companies need a systematic framework so innovation can occur at different levels of the organization. The world's leading expert in marketing and innovation Philip Kotler, and Fernando Trias de Bes together present a revolutionary model for innovation.
Keywords: INNOVATION